Thermotolerant wood rotting fungi isolated from northern Thailand and their potential uses in lignin degrading applications - Khanongnuch C. (2014)
One hundred and thirteen wood rotting taxa were isolated from northern Thailand. The isolate C. versicolor RC3 exhibited highly active growth at 37°C among 10 thermotolerant isolates including of strains ST40, TP7, TP16, NP14, NP18, NP21, NP26, NP27, 7M and C. versicolor strain RC3. Isolate RC3 was found to be Coriolus versicolor which degraded Poly R-478 dye at 42°C. Comparative growth studies on potato dextrose agar revealed that C. versicolor strain RC3 had almost the same growth rate as Phanerochaete chrysosporium strain ATCC 34541 at 37 and 42°C, while C. versicolor IFO30388 did not. When cultivated in the liquid basal medium containing 0.02% Poly R-478 dye at 37°C with 150 rpm shaking, C. versicolor strain RC3 degraded Poly R-478 dye completely within 5 days. This is more active than the well-researched lignin degrading white rot fungus, P. chrysosporium. Addition of 1%(w/v) glucose and 0.2%(w/v) NH4NO3 to the medium enhanced dye degradation. Coriolus versicolor strain RC3 removed the brown colour from rubber wood chips which changed the lightness from 37.05 to 46.07 of L* value without nutrients. This effect was not found in nutrient rich condition.